Hungary: Contracts in Labor Law - Jakab, Nóra (Fundamentals of Labor Law in Central Europe, 2022)
The employment contract and collective agreement have force if parties disclose this. Behind them is thefreedom of individual and collective will. In fact, the new employment relationships reflect this autonomyand the desire for it. For me, examining the dogmatics of the employment contract is not a matter of adapting Anglo-Saxon solutions, but of looking for the key to a solution in our rich private law literature. Indeed, in the field of civil law, this individual self-government is widespread, whereby legal entities themselves create the law for life relationships not compellingly regulated by law, or for unregulated parts of them. In labor law, therefore, I believe that it is in the employment contract that the law-making power of individuals must be rediscovered, for which the principle of partnership is essential. And the collective agreement is the key to the fulfillment of this partnership.Keywords: codification, employment contract, collective agreement, atypical employment law, relationship between labor law and civil law